2016
DOI: 10.1007/s00792-016-0874-2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and altitudinal changes of culturable bacterial and yeast diversity in Alpine forest soils

Abstract: The effect of altitude and season on abundance and diversity of the culturable heterotrophic bacterial and yeast community was examined at four forest sites in the Italian Alps along an altitude gradient (545–2000 m). Independently of altitude, bacteria isolated at 0 °C (psychrophiles) were less numerous than those recovered at 20 °C. In autumn, psychrophilic bacterial population increased with altitude. The 1194 bacterial strains were primarily affiliated with the classes Alpha-, Beta-, Gammaproteobacteria, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 90 publications
(127 reference statements)
5
38
1
Order By: Relevance
“…The rare yeast species formed 28% to 61% of the total yeast population associated with the soil of individual fruit tree species. Our results corroborate other authors' findings on the proportions of rare yeasts isolated from forest, grassland, and shrubland soils (França et al, ; Vishniac, ; Yurkov et al, ) and show that they can be considered common members of soil yeast microbiota.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The rare yeast species formed 28% to 61% of the total yeast population associated with the soil of individual fruit tree species. Our results corroborate other authors' findings on the proportions of rare yeasts isolated from forest, grassland, and shrubland soils (França et al, ; Vishniac, ; Yurkov et al, ) and show that they can be considered common members of soil yeast microbiota.…”
Section: Discussionsupporting
confidence: 93%
“…The present study discovered Apiotrichum species in the soil adjacent to the fruit trees in all samplings, over the 3 years, in both localities, and confirms their widespreadness. However, S. podzolica , Solicoccozyma aeria and Goffeauzyma gastrica , which also dominate the yeast microbiota in soil (França, Sannino, Turchetti, Buzzini, & Margesin, ; Groenewald et al, ; Yurkov, ), were isolated only rarely, similar to the results obtained with urban soil in Russia (Tepeeva et al, ).…”
Section: Discussionsupporting
confidence: 80%
“…The culture dependent method has some limitations such as many species fail to grow on the plate surface at all of a given medium and may be the dominant species on the plate surface are less which underestimate the richness of the sample [ 50 ]. Though the culturable techniques have some limitations to estimate the microbial population in environmental samples, however, it has the potential to demonstrate to retrieve both abundant and rare taxa in different environmental samples [ 51 ]. Thirty three representative isolates were selected from each group of the dendrogram generated by BOX-PCR genotyping and ARDRA profile, and they were identified by 16S rRNA gene sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast species play an important ecological role; they participate in processes such as decomposition of organic matter, soil aggregation, nutrient cycling in the soil (e.g., phosphate solubilization), biocontrol of soil pathogens, and plant growth promotion (Botha, 2011). Yeasts species occur in a wide range of different types of soil in the world (Stringini et al, 2008;Mestre et al, 2011;Yurkov et al, 2012a;Glushakova et al, 2015;França et al, 2016). Our knowledge about soil yeasts is biased towards temperate and boreal forests.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to point out that these authors focused only on soil filamentous fungi, whereas the distribution and dispersion abilities of yeast fungi can be different. With regard to the effect of altitude on soil yeast, França et al (2016) observed that the yeast species composition altered along an altitude gradient in Alpine forest soils during the spring season. However, the Brazilian forests differ substantially from Subalpine forest community in terms of species diversity, climate, and seasonality.…”
Section: Introductionmentioning
confidence: 99%